2014
DOI: 10.1002/app.40501
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and ultraviolet‐curing behaviors of vinyl ether functionalized polyurethane oligomers

Abstract: The vinyl ether functionalized oligomer is one of the most basic components of vinyl ether functionalized materials for cationic UV-curable coatings. In this study, three types of vinyl ether functionalized polyurethane oligomers (i.e., polyether, polyester, and polydimethylsiloxane) were synthesized with diisocyanate, diol, and hydroxyethyl vinyl ether. These oligomers were characterized by IR, 1 H-NMR, and 13 C-NMR spectroscopy. The effect of the raw material ratio on the oligomer, UV-curing behaviors, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…13 It was found that interactions with urethane groups can lead to reduced polymerization rates or yield products with reduced molecular weight and broadened polydispersity, thus indicating that transfer reactions cannot be completely prevented. Vinyl ether terminated urethane prepolymers9, 14 with cationic curing ability were synthesized but they still require blending with multifunctional reactive diluents to obtain higher crosslinking densities and a more distinct mechanical modulus increase upon polymerization. Recently, the first polymer systems bearing vinyl ether moieties along the backbone were reported, prepared as biocompatible polyether15 and polyphosphorester16 templates for post‐polymerization modification through thiol–ene “click” reactions.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…13 It was found that interactions with urethane groups can lead to reduced polymerization rates or yield products with reduced molecular weight and broadened polydispersity, thus indicating that transfer reactions cannot be completely prevented. Vinyl ether terminated urethane prepolymers9, 14 with cationic curing ability were synthesized but they still require blending with multifunctional reactive diluents to obtain higher crosslinking densities and a more distinct mechanical modulus increase upon polymerization. Recently, the first polymer systems bearing vinyl ether moieties along the backbone were reported, prepared as biocompatible polyether15 and polyphosphorester16 templates for post‐polymerization modification through thiol–ene “click” reactions.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…After the chlorination of LHBPCS, a new absorption peak corresponding to Si–Cl group appeared at 460–490 cm −1 . 16–30 After incorporating the 2‐HEVE, the absorption peak corresponding to Si–Cl group disappeared, and the absorption peaks corresponding to vinyl ether group appeared at 3116 cm −1 (=C–H stretching), 1616 cm −1 (C=C stretching), and 1219 cm −1 (=C–O stretching) 31,32 . In addition, compared with the raw LHBPCS, the intensity of peaks at 2930 and 2880 cm −1 (C–H stretching of linkage structure –CH 2 –CH 2 –O–) increased significantly 33 .…”
Section: Resultsmentioning
confidence: 97%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] After incorporating the 2-HEVE, the absorption peak corresponding to Si-Cl group disappeared, and the absorption peaks corresponding to vinyl ether group appeared at 3116 cm −1 (=C-H stretching), 1616 cm −1 (C=C stretching), and 1219 cm −1 (=C-O stretching). 31,32 In addition, compared with the raw LHBPCS, the intensity of peaks at 2930 and 2880 cm −1 (C-H stretching of linkage structure -CH 2 -CH 2 -O-) increased significantly. 33 Meanwhile, the absorption peak corresponding to the hydroxy group of 2-HEVE did not exist and the absorption peak corresponding to Si-O stretching at 1100-1050 • cm −1 appeared in the FT-IR spectrum of VE-LHBPCS, indicating the condensation reaction between chlorinated LHBPCS and 2-HEVE proceeded.…”
Section: Preparation Of Ve-lhbpcsmentioning
confidence: 95%
“…13 Dabei wurde festgestellt, dass Übertragungsreaktionen nicht vollkommen vermieden werden können und die Anwesenheit von Urethangruppen teilweise zu reduzierten Polymerisationsgeschwindigkeiten oder Produkten mit vermindertem Molekulargewicht und breiteren Molekulargewichtsverteilungen führt. Auch endständig vinyletherfunktionalisierte Urethanpräpolymere wurden hergestellt,9, 14 benötigen aber multifunktionelle Reaktivverdünner, um hohe Vernetzungsdichten und einen deutlicheren Anstieg des mechanischen Moduls durch kationische Polymerisation hervorzurufen. Kürzlich wurden erstmals Polymere mit Vinylethern entlang des Polymerrückgrats beschrieben.…”
Section: Thermische Eigenschaftenunclassified